Effects of COVID-19 Pandemic on International Capital Markets - Souza, Paulo Vitor Souza de; Tibúrcio Silva, César Augusto (International Journal of Economics and Financial Issues, 2020)
In this paper, we analyzed the effects of the crisis generated by the COVID-19 pandemic on international capital markets. We used the most representative indexes belonging to the stock markets of 44 world economies in daily time series with data from 01/02/2019 to 05/15/2020. Correlation analysis and average price tests, graphical analysis of returns, and multiple linear regression analysis of index efficiency were made, together with the cultural dimensions and macroeconomic aspects of the markets. The findings provide evidence that in the periods after the pandemic, the markets became more correlated by increasing the correlation levels of their indexes. We found a significant difference in the correlation coefficients of the periods before and after the pandemic, indicating a change in behavior of the correlation indexes. Markets presented a reduction in their returns and an increase in their volatility after the pandemic. The pandemic affected the efficiency behavior of the market indexes. In the pre-pandemic period reduced the market’s efficiency by individualism and aversion to uncertainty and increased inflation. In the post-pandemic period, efficiency was increased by individualism and reduced by indulgence. These results provide evidence that the behavior of efficiency changed, indicating an adaptive behavior of international capital markets. Keywords: Economic Crisis, Uncertainty, Pandemic, Adaptive Markets. JEL Classifications: G14, G15, G41. DOI: https://doi.org/10.32479/ijefi.10702